2004
DOI: 10.1097/00001888-200408000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Improving Knowledge in Palliative Medicine with a Required Hospice Rotation for Third-Year Medical Students

Abstract: This 32-hour required curriculum in palliative medicine for third-year medical students improved knowledge. They came to the course with appropriate attitudes that did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 10 publications
2
59
0
Order By: Relevance
“…6,12,20 Furthermore, female students were more concerned about to the prospect of being confronted with suffering and death in later professional life compared to the male students. Correspondingly, female students attached higher importance to ''self-reflection regarding their own role as a physician caring for the terminally ill and dying patients along with psychological support'' as well as to palliative care teaching as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,20 Furthermore, female students were more concerned about to the prospect of being confronted with suffering and death in later professional life compared to the male students. Correspondingly, female students attached higher importance to ''self-reflection regarding their own role as a physician caring for the terminally ill and dying patients along with psychological support'' as well as to palliative care teaching as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…41 Specific education sessions have been found to improve attitudes toward PC, 44 but the durability of such change is unknown; others have found no improvement in attitudes after hospice and PC electives. 45 Although medical school curricula have increased the time allocated to PC over recent years, the impact has been variable. 46 These uncertain, and at times contradictory, results from the literature may reflect in part the cross-sectional and small scale of many previous studies; the present study is novel in being one of the largest studies to date and in the longitudinal data analysis undertaken.…”
Section: Comparison With the Wider Literaturementioning
confidence: 99%
“…Of the nine studies analyzed, three identified third-year medical students as participants. [8][9][10] Two studies indicated their subjects were fourth-year medical students. 11,12 Only one study focused on first-year medical students.…”
Section: Introduction Of Curriculummentioning
confidence: 99%